Answer: The required solution of the given IVP is
![y(x)=\dfrac{3}{4}e^x+\dfrac{5}{4}e^{-x}.](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdfrac%7B3%7D%7B4%7De%5Ex%2B%5Cdfrac%7B5%7D%7B4%7De%5E%7B-x%7D.)
Step-by-step explanation: We are given to find the solution of the following initial value problem :
![y^{\prime\prime}-y=0,~~~y(0)=2,~~y^\prime(0)=-\dfrac{1}{2}.](https://tex.z-dn.net/?f=y%5E%7B%5Cprime%5Cprime%7D-y%3D0%2C~~~y%280%29%3D2%2C~~y%5E%5Cprime%280%29%3D-%5Cdfrac%7B1%7D%7B2%7D.)
Let
be an auxiliary solution of the given differential equation.
Then, we have
![y^\prime=me^{mx},~~~~~y^{\prime\prime}=m^2e^{mx}.](https://tex.z-dn.net/?f=y%5E%5Cprime%3Dme%5E%7Bmx%7D%2C~~~~~y%5E%7B%5Cprime%5Cprime%7D%3Dm%5E2e%5E%7Bmx%7D.)
Substituting these values in the given differential equation, we have
![m^2e^{mx}-e^{mx}=0\\\\\Rightarrow (m^2-1)e^{mx}=0\\\\\Rightarrow m^2-1=0~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^{mx}\neq0]\\\\\Rightarrow m^2=1\\\\\Rightarrow m=\pm1.](https://tex.z-dn.net/?f=m%5E2e%5E%7Bmx%7D-e%5E%7Bmx%7D%3D0%5C%5C%5C%5C%5CRightarrow%20%28m%5E2-1%29e%5E%7Bmx%7D%3D0%5C%5C%5C%5C%5CRightarrow%20m%5E2-1%3D0~~~~~~~~~~~~~~~~~~~~~~~~~~%5B%5Ctextup%7Bsince%20%7De%5E%7Bmx%7D%5Cneq0%5D%5C%5C%5C%5C%5CRightarrow%20m%5E2%3D1%5C%5C%5C%5C%5CRightarrow%20m%3D%5Cpm1.)
So, the general solution of the given equation is
where A and B are constants.
This gives, after differentiating with respect to x that
![y^\prime(x)=Ae^x-Be^{-x}.](https://tex.z-dn.net/?f=y%5E%5Cprime%28x%29%3DAe%5Ex-Be%5E%7B-x%7D.)
The given conditions implies that
![y(0)=2\\\\\Rightarrow A+B=2~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://tex.z-dn.net/?f=y%280%29%3D2%5C%5C%5C%5C%5CRightarrow%20A%2BB%3D2~~~~~~~~~~~~~~~~~~~~~~~~~~~%28i%29)
and
![y^\prime(0)=-\dfrac{1}{2}\\\\\\\Rightarrow A-B=-\dfrac{1}{2}~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=y%5E%5Cprime%280%29%3D-%5Cdfrac%7B1%7D%7B2%7D%5C%5C%5C%5C%5C%5C%5CRightarrow%20A-B%3D-%5Cdfrac%7B1%7D%7B2%7D~~~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
Adding equations (i) and (ii), we get
![2A=2-\dfrac{1}{2}\\\\\\\Rightarrow 2A=\dfrac{3}{2}\\\\\\\Rightarrow A=\dfrac{3}{4}.](https://tex.z-dn.net/?f=2A%3D2-%5Cdfrac%7B1%7D%7B2%7D%5C%5C%5C%5C%5C%5C%5CRightarrow%202A%3D%5Cdfrac%7B3%7D%7B2%7D%5C%5C%5C%5C%5C%5C%5CRightarrow%20A%3D%5Cdfrac%7B3%7D%7B4%7D.)
From equation (i), we get
![\dfrac{3}{4}+B=2\\\\\\\Rightarrow B=2-\dfrac{3}{4}\\\\\\\Rightarrow B=\dfrac{5}{4}.](https://tex.z-dn.net/?f=%5Cdfrac%7B3%7D%7B4%7D%2BB%3D2%5C%5C%5C%5C%5C%5C%5CRightarrow%20B%3D2-%5Cdfrac%7B3%7D%7B4%7D%5C%5C%5C%5C%5C%5C%5CRightarrow%20B%3D%5Cdfrac%7B5%7D%7B4%7D.)
Substituting the values of A and B in the general solution, we get
![y(x)=\dfrac{3}{4}e^x+\dfrac{5}{4}e^{-x}.](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdfrac%7B3%7D%7B4%7De%5Ex%2B%5Cdfrac%7B5%7D%7B4%7De%5E%7B-x%7D.)
Thus, the required solution of the given IVP is
![y(x)=\dfrac{3}{4}e^x+\dfrac{5}{4}e^{-x}.](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdfrac%7B3%7D%7B4%7De%5Ex%2B%5Cdfrac%7B5%7D%7B4%7De%5E%7B-x%7D.)